Pelatihan Peningkatan Akreditasi Jurnal Berbasis OJS 3 (Open Journal System) di Lingkungan Universitas Almuslim Kabupaten Bireuen - Irfannur; Yusrizal Akmal; Muliari Muliari; Syahirman Hakim; Rinaldi Rinaldi (Aceh Journal of Community Engagement (AJCE), 2023)
Lecturer service activities in the form of training aim to increase participants' understanding and ability in managing the OJS website and the use and application of OJS in managing online journals. The training method is divided into three stages, namely the planning and implementation stages, the activity observation stage and the activity evaluation stage. The results of the activity follow the flow following material on the introduction of OJS 3 which outlines journal publishing, the initial process of publishing a journal through the OJS portal (Open Journal System) and journal managers are introduced to website features. The target for managing journals currently managed is to be accredited nationally (SINTA). Furthermore, as a benchmark for respondents participating in the training, it can be analyzed in the question and answer session of participants to journal sources.